Response to trastuzumab deruxtecan and delayed immune-related events in a patient with metastatic HER2-positive NSCLC: a case report and literature review - Wang, Lu; Wen, Shidi; Zhu, Wenjia; Zhang, Zhiyang; Cheng, Yuejuan (Frontiers in Oncology, 2025)
Trastuzumab deruxtecan (DS-8201) is an antibody-drug conjugate (ADC) designed to target HER2 mutations. We reported a case study demonstrating a favorable response to DS-8201 in a patient with HER2 mutation-positive non-small cell lung cancer (NSCLC) who exhibited resistance to initial immunotherapy, along with delayed immune-related events of hypoadrenocorticism occurring five months after discontinuation of immune checkpoint inhibitors. After reviewing the relevant literature, we discussed the mechanism of ADC agents underlying their anti-tumor activity and the potential impact of DS-8201 on the tumor microenvironment. This case highlights the efficacy of DS-8201 in NSCLC, particularly in individuals who have failed first-line immunotherapy, and provide valuable insights for clinicians exploring innovative strategies for the management of patients with lung cancer.